Soveršenstvovanie strel'by biatlonistov s ispol'zovaniem trenažërnogo kompleksa «SCATT» - Sergeev, G. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The present study introduces the sport specific exercises that could be performed by using "SCATT" training equipment. These exercises were developed for shooting technique enhancement in biathletes. The developed complex of shooting exercises is especially focused on such element of shooting as "holding". Shooting was performed by the use of small caliber rifle Bi 7-4 and "SCATT" shooting equipment. The results showed that the experimental group has significantly increased shooting accuracy in prone and standing shooting positions. An average trajectory of aiming point movement (mm) during 2 sec of control time was significantly smaller in experimental group compare to control group in both prone and standing shooting. The analysis of aiming point movement speed in time frame of 250 ms before shot, showed that the experimental group had significantly better results in both prone and standing shooting positions compare to the control group. This parameter reflects how stable the link between a rifle and athlete is during the trigger processing. Taking all above mentioned into consideration it could be concluded that presented exercises are the effective tool for shooting accuracy improvement and they should be included in the training process of biathletes.